DEVELOPMENT OF STEM-PjBL BASED STUDENT ACTIVITY SHEETS ON GREEN CHEMISTRY TOPIC TO SUPPORT STUDENTS’ COLLABORATION SKILLS - Elsa Kharisma Zulaicha; Mitarlis Mitarlis (Universitas Negeri Surabaya, 2026)
Emerging global issues require learning media to support students' collaboration skills to connect concepts and design solutions in order to solve contextual problems. This study aims to describe feasibility of student activity sheet (SAS) based on STEM (Science, Technology, Engineering, and Mathematics) approach and project-based learning on the topic of green chemistry to support collaboration skills. This research employed a research and development (R&D) method using 4D model, limited to the Define, Design, and Develop stages. The limited trial involved 32 tenth-grade students at a Senior High School in Surabaya. The research instruments include validation sheets, student response questionnaires, learning implementation observation sheets, student activity observation sheets, and collaboration skills self-assessment. Data were analyzed descriptively using median scores and percentages. The validity of SAS was assessed by two chemistry lecturers and one chemistry teacher with median 5 categorized as very valid criteria. The practicality of SAS was measured through student response questionnaires, obtaining percentage of 96,88% categorized as very practical criteria, learning implementation observation with median 5 categorized as very good criteria, and student activity observation with percentage of 94,56% categorized as very good criteria. The effectiveness of SAS was measured through collaboration skills self-assessment, obtaining 86,06% in the first meeting and 93,31% in the second meeting both categorized as very good. These findings indicate that the developed SAS is feasible for supporting students’ collaboration skills in green chemistry topic.